Pengaruh Penggunaan Metode ECOLA Terhadap Kemampuan Menulis Teks Prosedur Peserta Didik Kelas XI MA Bustanul Ulum Pagerharjo Tahun Pelajaran 2022/2023 - Salma Khoirun Nisa (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
This study aims to determaine whether there is an influence in the use of the ECOLA method on the ability to write procedural texts for students of class XI MA Bustanul Ulum Pagerharjo in the 2022/2023 academic year. In this research is a type of quantitative descriptive research. Data collection is done by testing techniques. Data analysis is presented in the form of table numbers, diagrams, and descriptions. The results of the analysis from this study are that there is an influence in the use of the ECOLA method on the ability to write procedural texts of students for the 2022/2023 school year. This can be proven from the results of hypothesis test, namely t count from the results the pretest dan posttest were 1,6627 an the results from the t table pretest and posttest were 2.015368. Thus it can be concluded that Ho is rejected and Ha is accepted, because t-table>t-count. So based on the hypothesis test calculations above, it can be said that use of the ECOLA method affects the ability to write procedural texts for students of class XI MA Bustanul Ulum Pagerharjo in the 2022/2023 academic year.